A Grammatical Comparison of Malay and Tagalog - Lopez, Cecilio (The Archive, 2025)
Excerpt It is perhaps superfluous to repeat here what is already known even to the layman, that Malay and Tagalog have many items in common in their vocabularies. What is likely not generally known, however, is that while there are some features in grammar which the two languages share, there are many more in which they differ. My purpose in making this comparison is to show the average speaker of Malay and Tagalog how each other’s language looks like. To be sure, their cultures had been under foreign influences for centuries, again a well-known fact, and these influences had bestowed a largess in the languages of the former wards, particularly in their vocabularies: the Malays predominantly under British, Dutch and Islam, the Tagalogs under Spanish, American and Christian influences.